Perspectives Future Research in Conceptual Change for Science Education: Systematic Literature Review - Bin Amiruddin, Mohd Zaidi; Suhandi, Andi; Samsudin, Achmad; Costu, Bayram; Kaniawati, Ida (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Conceptual change refers to the process through which individuals revise and restructure their understanding of scientific concepts, often replacing misconceptions with scientifically accurate knowledge. This article presents a systematic review of research on conceptual change in science education from 2021 to 2023, analysing 28 articles identified through a predefined keyword search. Employing the systematic literature review methodology, the study applied inclusion, exclusion, and quality screening criteria using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) technique. The findings highlight a predominant focus on qualitative approaches, such as interviews and observations, to investigate cognitive and social factors influencing students' learning processes. The review also identifies significant research gaps, including the need for more comprehensive assessment tools and interdisciplinary approaches to facilitate effective conceptual restructuring. The implications of this study suggest that educators should adopt adaptive teaching strategies, while policymakers should design curricula that promote conceptual change-based learning. Future research should prioritise refining methodologies, exploring the long-term effects of conceptual interventions, and leveraging technology to enhance science education.
Keywords: alternative conception; assessment tools; conceptual change; science education; student outcomes; UNDERGRADUATE STUDENTS; MISCONCEPTIONS; TEACHERS; DIFFICULTIES; FRAMEWORK; MODELS; Education & Educational Research